APOE gene polymorphism as a potential predictor of postoperative cognitive dysfunction in colon cancer surgery under general anesthesia - Bošković, Dalibor; Marić, Sanja; Lalović, Nenad; Mašić, Srdjan; Elez-Burnjaković, Nikolina; Miletić, Rade; Spaić, Dragan; Krunić, Jelena (Vojnosanitetski pregled, 2025)
Background/Aim. Postoperative cognitive dysfunction (POCD) occurs very often in operated patients. This increasingly frequent complication compromises the recovery of operated patients, impairs the quality of life of patients and their families, prolongs the length of hospital stay, and increases the cost of treatment. The aim of the study was to examine the association between the apolipoprotein E (APOE) ε4 allele and sociodemographic and clinical characteristics with the occurrence of POCD seven days and three months after colon cancer surgery (CCS) under general anesthesia (GA). Methods. A total of 113 patients aged 18 to 87 years who underwent CCS under GA in the period from 2021 to 2023 participated in the study. Preoperative preparation, anesthesia, and postoperative treatment were uniform and standardized for all patients. The assessment of cognitive status was conducted using the Mini Mental State Examination psychometric test on the day before surgery, on the seventh postoperative day, and three months after surgery. Results. Seven days after surgery, a statistically significant impairment of cognitive functions was found in patients with the APOE ε4 allele in their genotype (p = 0.007). Patients 65 years old or above were more likely to have POCD three months after surgery compared to younger patients (80.0% vs. 52.9%; p = 0.003). Conclusion. The presence of the APOE ε4 allele is a potential predictor of the occurrence of POCD seven days after surgery, and age is a significant sociodemographic factor for the occurrence of POCD three months after CCS is performed under GA.